Assessing Cause of Defect Using Failure Mode and Effect Analysis - Rahmawati, Berty Dwi; Maharani, Nadia Nisya Budi (Universitas Ahmad Dahlan, 2023)
A company should implement good quality management to maintain consumer confidence in producing quality products. FMEA serves to identify product failures in a process and the causes of defects or losses that occur during the production process of a product, component, or system. The research aims to analyze quality control and identify production defects that cause a decrease in quality. The samples studied were rejected goods in production activities. Forty damaged parts were used as the samples in this study. This study used both qualitative and quantitative analysis. Quantitative analysis was conducted to determine the type of rejection and then to rank the risk, while qualitative analysis was performed with Ishikawa diagram to evaluate risk priorities. This research not only helps identify and assess the root cause of rejected goods but also affects the following year's planning by proposing measures to reduce risk. Check sheets and histograms are used to present further research. The analysis results show two classifications of defects in production: size error and painting error, with the most dominant defect, size error, and equal to 73.17%. Based on the analysis of the causes of defects, several factors were found that caused product defects; man, material, method, machine. The man factor has the highest value in contributing to defect, with an RPN score of 192.